SOCIAL NETWORK AND LANGUAGE ABILITY OF THE KEJAMAN COMMUNITY FROM BELAGA, SARAWAK, MALAYSIA - Amee, Joan; Ting, Su Hie (2021)
The Kejaman are a small indigenous group living in the interior of Belaga, along the Balui River, in the Kapit Division of Sarawak, Malaysia. The study examined the role of social network on the language ability of the Kejaman speakers from Belaga, Sarawak, Malaysia. Using questionnaires, data were collected from 123 participants from three generations of the Kejaman speakers from two longhouses (Rumah Kejaman Neh Long Litten and Rumah Kejaman Ba Segaham) in Belaga, Sarawak. The study employed Milroy's (1987) framework for social network analysis. The results for language ability showed a marked difference between the older generation and the younger generation. The first and second generations were able to interact fluently and spontaneously using their mother tongue. The second generation was more versatile in terms of language ability as they were fluent speakers of many languages. The ability to use the Kejaman language declined significantly among the third generation. In terms of social networks, the findings showed that exchange networks played an important role in the lives of the Kejaman community. The results revealed a negative significant correlation between the density of the participants’ social network and language ability.